1992
DOI: 10.1002/pola.1992.080300521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of degradation on thermotropic cholesteric optical properties of (2‐hydroxypropyl) cellulose (HPC) esters

Abstract: SYNOPSISSome esters of (2-hydroxypropyl) cellulose have been prepared and studied. Their cholesteric properties change with ageing and may disappear. Accelerated aging has been performed in order to analyze degradation processes which are relevant to the scission of the polymeric main chain and to the hydrolysis of the ester bonds which are mainly due to traces of water. The necessity of carefully elaborate purification is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The esters presented in Table I were prepared without solvent at room temperature from the corresponding acid chlorid and ( 2-hydroxypropyl) cellulose [Hercules Klucel E, = 120,000 g/mol, with a degree of substitution (m) of 2.5 and a molar substitution (m) of 3.751 according to the procedure described previously. 12 In the case of BPC, two different procedures were used. To obtain different extents of esterification, we used different amounts of acid chloride for 10 g ( 3 equiv) of HPC.…”
Section: Methodsmentioning
confidence: 99%
“…The esters presented in Table I were prepared without solvent at room temperature from the corresponding acid chlorid and ( 2-hydroxypropyl) cellulose [Hercules Klucel E, = 120,000 g/mol, with a degree of substitution (m) of 2.5 and a molar substitution (m) of 3.751 according to the procedure described previously. 12 In the case of BPC, two different procedures were used. To obtain different extents of esterification, we used different amounts of acid chloride for 10 g ( 3 equiv) of HPC.…”
Section: Methodsmentioning
confidence: 99%
“…The generic synthesis of (Acetoxypropyl)cellulose is described in detail in Rusig et al (1992), Tseng et al (1981), and Costa et al (2007). In our case we had the following modifications: acetilation of (hydroxypropyl)cellulose (HPC) (Aldrich, nominal M w = 100,000, molar substitution equal to 4 as determined by 1 H NMR) (50 g) was performed by adding the HPC to acetic anhydride (160 g).…”
Section: Experimental Partmentioning
confidence: 99%
“…The rheological behavior of HPC derivatives possessing acyl groups is interesting. Previous studies reported that sticky products are obtained by acylation of HPC [3,4,[8][9][10]. This phenomenon is quite strange in that sticky polymer melts are produced from a powdery raw material of pristine HPC after the simple acylation.…”
Section: Introductionmentioning
confidence: 99%